Outcome of Open Enucleation with Capitonnage for Hydatid Lung Disease in Children - Jamil Ur Rehman; Raza, Tahir; Hussain, Saddam; Khan, Hamdan; Khan, Muhammad Abid (Indus Journal of Bioscience Research, 2025)
Introduction: Hydatid cystic disease remains an endemic surgical problem in many part of world including Indian subcontinent. Most commonly involved organs are the liver (60%-80%) and the lung (10%-40%) but it can involve any part of body. Surgery is preferable treatment of pulmonary hydatid among various surgical procedure open enucleation with capitonnage is preferred procedure. Objectives: To determine outcome of open enucleation with capitonnage for hydatid lung disease in children in term of postoperative complications and length hospital stay. Materials and Methods: This descriptive study was conducted at Thoracic Surgery Ward of Lady Reading Hospital (LRH), Peshawar between September 2023 and February 2024. A total of 118 patients were included in the study fulfilling the inclusive criteria. Results: Open enucleation with cappitonage were performed in 118 patients with pulmonary hydatid disease. The 57.4% were male and 42.6% female, and their mean age was 10.4 ± 3.2 years. 24.6% patients developed complication after surgery. Surgical site infection was the most frequent complication, reported in 6.8% of cases, followed by atelectasis (5.1%) and pneumothorax and surgical emphysema were observed in 4.2% of the patients, prolonged air leak 3.4% and 2.5% of patients developed empyema and residual cavity. Surprisingly, no mortality was reported among the patients who underwent surgery in this study. Conclusion: Thus, open enucleation with capitonnage is still considered safe and effective in paediatric hydatid disease with tolerable complications and good postoperative recovery.